2021
DOI: 10.1016/j.jqsrt.2020.107495
|View full text |Cite
|
Sign up to set email alerts
|

Validation of spectroscopic data in the 1.27 µm spectral region by comparisons with ground-based atmospheric measurements

Abstract: Various spectroscopic data for absorption lines due to the magnetic dipole transitions of the ∆ − Σ (0 − 0) band of O2 centered at 1.27 m are tested by comparison with highresolution ground-based atmospheric measurements recorded by Fourier Transform Spectrometers at Park Falls and Caltech (USA). This band is of importance for atmospheric remote sensing since it will be used (together with the O2 A-band near 760 nm) by the passive short wave infrared spectrometer onboard the MicroCarb satellite mission (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Where ρ are densities in amagat, BO2O2and BO2N2 are the binary collision absorption coefficients in cm −1 amagat −2 . MO2(ν)ρO2 is the local monomer contribution due to the 1.27 µm band of O 2 that was generated using the most recent spectroscopic data [see (Tran et al., 2021) and references therein]. A speed dependent Nelkin‐Ghatak profile was used for these intense lines and a Voigt profile for the others, with a cutoff value of ±5 cm −1 from the line center.…”
Section: Spectra Analysismentioning
confidence: 99%
“…Where ρ are densities in amagat, BO2O2and BO2N2 are the binary collision absorption coefficients in cm −1 amagat −2 . MO2(ν)ρO2 is the local monomer contribution due to the 1.27 µm band of O 2 that was generated using the most recent spectroscopic data [see (Tran et al., 2021) and references therein]. A speed dependent Nelkin‐Ghatak profile was used for these intense lines and a Voigt profile for the others, with a cutoff value of ±5 cm −1 from the line center.…”
Section: Spectra Analysismentioning
confidence: 99%
“…The study by Mendonca et al (2019) is the first to show the need for a spectral line shape that takes into account speed-dependence. Since then, newer spectroscopic studies such as Tran et al (2020) and Fleurbaey et al (2021) Tran et al (2021). The study showed that the newer spectroscopic parameters slightly improved the quality of the spectral fit but they should also be assessed on how they impact the airmass dependence of retrieved O 2 columns.…”
Section: Telluric and Solar Line Listsmentioning
confidence: 99%
“…In the initial CRDS study of CIA in the 1. 27 [12]. The broad wavenumber ranges covered, 7550 cm − 1 -8360 cm − 1 at 271 K and 332 K, and cm − 1 -8466 cm − 1 at 297 K, were achieved using a combination of distributed feedback and external cavity diode lasers.…”
Section: Experimental and Theoretical Ciamentioning
confidence: 99%
“…Unlike the Maté et al data [14], these spectra were collected below 1 amagat (which is more representative of atmospheric conditions), and measurements were made in the troughs between the monomer absorption lines. As described above, the CIA was determined as the remaining absorption after having subtracted the measured Rayleigh scattering and monomer absorption [26,27]. The reported binary collision absorption coefficient was based on a spline fit to the CIA measurements in the trough segments.…”
Section: Experimental and Theoretical Ciamentioning
confidence: 99%